Assessment of the knowledge of college students in Vale do Paraíba – SP about HIV and Syphilis infection (Research, Society and Development, 2023)
The goal of the study was to evaluate the knowledge and perception of risk in relation to sexually transmitted infections (STIs) among students in the universities of Vale do Paraíba, in the city of Pindamonhangaba. Using the qualitative method, following the guidelines of Souza Martins and based on the participation of 100 university students of both sexes aged between 18 and 44 years old, matriculated in higher education from 20 April to 1 July of 2023. Approved by the ethics committee (CAAE n 65830822.7.0000.8116). Using the Google Forms platform, university students from Vale do Paraíba – SP answered to the questionnaire, after reading the demonstrations, all the data was analyzed and calculated through descriptive statistics, for the arithmetic mean calculation, master plan, interval of confiança e porcentagens, como auxílio de software Microsoft Office Excel®. The results highlight the need to begin education about STIs for university students, especially those in the healthy area, to prepare them best for personal and collective health care. The STI prevention campaigns must be revised and modernized to effectively address the young population. Higher education institutions must promote more in-depth research into public health, emphasizing the importance of preventing and combating STIs. This study addresses the need for a more effective approach to education about STIs among university students, given a high level of knowledge and behaviors identified in the population.